Autores - Rivas, Ramón D. (Kóot, 2016)
Carmen Molina Tamacas Rubén Fúnez Iliana Stephanie Arias Salegio Luis Alberto Ambroggio Pablo de Jesús Castro H. Rhina Toruño-Haensly Ramón D. Rivas Julio Martínez Carlos Osegueda David Hernández